Anxiety and life satisfaction in adolescents: the mediating role of emotional dysregulation - Bolaños Rueda, Jeancarlo Joel (2024)
Objective. To examine the mediating role of emotional dysregulation between anxiety and life satisfaction in adolescents from Metropolitan Lima (Peru). Methods. A quantitative, crosssectional, and predictive design was used. The sample, selected by convenience, included 522 adolescents (52.3% males; 47.7% females) with an average age of 15.41 years. The instruments used were the GAD-7 to measure anxiety, the SWLS to assess life satisfaction, and the EDSshort for emotional dysregulation. Data were analyzed using a structural equation model, employing the weighted least squares mean and variance adjusted (WLSMV) estimator. Results. Anxiety had a direct impact on emotional dysregulation (B = 0.67; p < 0.001) and a negative impact on life satisfaction (B = -0.12; p < 0.036). Additionally, emotional dysregulation alsohad a signifIcant negative effect on life satisfaction (B = -0.17; p < 0.003). Mediation analysis revealed that emotional dysregulation fully partially the relationship between anxiety and life satisfaction (indirect effect B = -0.12; p < 0.003). Conclusions. Emotional dysregulation is a key mediator in the relationship between anxiety and life satisfaction in adolescents, highlighting the importance of addressing both anxiety and emotional regulation in interventions to improve the mental well-being of adolescents.